Metalenses : advances and applications - Tseng, Ming Lun (2020)
Metasurfaces, the 2D counterpart of artificial metamaterials, have attracted much attention because of their exceptional ability to manipulate the electromagnetic wave such as amplitude, phase, polarization, propagation direction, and so on. Different from conventional lenses, metalenses based on the metasurface optics are truly flat and compact and exhibit superior performance. In this report, recent progress in the development of metalenses is explored. First, the working principle and characteristics of metalenses are discussed. Then, it is described how the dispersion aberration in metalenses can be eliminated to make them suitable for being employed in a range of applications that are difficult or impossible for traditional lenses. In addition, various metalens‐based applications are introduced, including imaging, high spectral resolution spectroscopy, and multiplex color routing. Furthermore, a survey of reconfigurable and tunable metalenses is conducted. Finally, the report concludes by addressing future prospects of metalenses.